(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2021)
The purpose of this article was to develop an understanding of the value of knowledge andskills, as well as theories and ideas. A qualitative study was conducted to investigate the value, theories,and conceptions of knowledge and skills, as well as individual capacities, using various online journals,publications, and across the globe.Because of the nature of investing in people as the major source ofcompany success, it has been discovered that knowledge and skills are the most crucial factors forbusiness success. Business performance, management, and operations are all linked to knowledge andskills. Knowledge and abilities, on the other side , have a good or negative impact on personal traits,customer happiness, and service quality.Various philosophers debated and contrasted the relevance of knowledge and skills, as well as theories,definitions, and acquisition techniques. They do, however, vary from period to time and from one scholarand philosopher to the next. This is due to the changes that occur inside an organisation, such astechnical developments, global economic changes, and the volatility of human resources as a result ofthese changes.The lack of information and skills, according to this article, may be a severe issue for anindividual’s perceptions and comprehension. It may also result in major consequences and problems forthe organization’s ability to carry out its activities in order to meet its planned aims and objectives. And,in order to avoid this harm, company owners, managers, and people must respond to the specified keyquestions(professionals and un-professionals)